2014
DOI: 10.18632/oncotarget.2458
|View full text |Cite
|
Sign up to set email alerts
|

The tyrosine phosphatase PTPRO sensitizes colon cancer cells to anti-EGFR therapy through activation of SRC-mediated EGFR signaling

Abstract: Inappropriate activation of epidermal growth factor receptor (EGFR) plays a causal role in many cancers including colon cancer. The activation of EGFR by phosphorylation is balanced by receptor kinase and protein tyrosine phosphatase activities. However, the mechanisms of negative EGFR regulation by tyrosine phosphatases remain largely unexplored. Our previous results indicate that protein tyrosine phosphatase receptor type O (PTPRO) is down-regulated in a subset of colorectal cancer (CRC) patients with a poor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 52 publications
4
20
0
Order By: Relevance
“…Notably, non-selective SFK inhibitor PP2 (10 µM) decreased the phosphorylation of c-Src, Lyn, Syk, and EGFR ( Figure 1B). Because PP2 also reduced EGFR phosphorylation, we suggest there is a feedback loop to control EGFR activation through SFKs as previously reported in fibroblasts [23], breast [23,24], and colon cancer cells [25] in a transactivation manner. All these findings suggested that Syk is a signal molecule for EGFR, and its activation is downstream of SFKs.…”
Section: Sfk-dependent Syk Activation Mediates Downstream Signal Pathsupporting
confidence: 79%
“…Notably, non-selective SFK inhibitor PP2 (10 µM) decreased the phosphorylation of c-Src, Lyn, Syk, and EGFR ( Figure 1B). Because PP2 also reduced EGFR phosphorylation, we suggest there is a feedback loop to control EGFR activation through SFKs as previously reported in fibroblasts [23], breast [23,24], and colon cancer cells [25] in a transactivation manner. All these findings suggested that Syk is a signal molecule for EGFR, and its activation is downstream of SFKs.…”
Section: Sfk-dependent Syk Activation Mediates Downstream Signal Pathsupporting
confidence: 79%
“…Both CA12 and HMGCS2 are considered to be potential targets for cancer treatment. Of the remaining 8 genes, MS4A12 (30) and PTPRO (31) have been documented to be involved in the epidermal growth factor signaling pathway in CRC. TPI1 has been detected as an auto-antibody in the sera of CRC patients (32).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the cells were washed with PBS, fixed with methanol, and then stained with 0.5% crystal violet. Colonies were photographed and counted using Image J software [ 35 ].…”
Section: Methodsmentioning
confidence: 99%